2022
DOI: 10.31014/aior.1993.05.03.533
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect of 8-Week Life Kinetic Training on Self-Confidence, Attention and Psychological Skill Levels in Sedentary Men Students

Abstract: This research was conducted to examine the effect of 8-week life kinetic training on self-confidence, attention and psychological skill levels in sedentary men students. Fifteen sedentary men participated in the study and the research was conducted using the pretest-posttest research model. In order to collect the data, “D2 Test of Attention” developed by Brickenkamp (1981), “Self-confidence Scale” developed by Akın (2007), “Athletic Coping Skills Inventory” developed by Smith (1995) and personal information f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Similarly, in a study conducted by Yıldırım (2022), it was concluded that high school students who participate in sports activities tend to show higher levels of self-confidence. (Kilis 7 Aralık University, Turkey & Yildirim, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a study conducted by Yıldırım (2022), it was concluded that high school students who participate in sports activities tend to show higher levels of self-confidence. (Kilis 7 Aralık University, Turkey & Yildirim, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Self-confidence, which is one of the strong predictors of academic success and defined Bozgun & Akin ,2023) , is one of the important determinants of an individual's feelings, thoughts, behaviors, and motivation for certain tasks Bandura (1997); it is defined by Toy (2023) as " Self-confidence is the belief that an action can be carried out successfully is the state of an individual to develop positive and optimistic feelings and thoughts towards himself/herself and to feel good about himself/herself (Yildrim, 2022).…”
Section: Introductionmentioning
confidence: 99%